Role of neurosonogram in critical ill patients who is admitted in NICU - RAO, A.RUPESH; TAKSANDE, AMAR (International Journal of Psychosocial Rehabilitation, 2020)
Neonates who was born premature or sick preterm and term are likely to developed cns abnormality,neurosonogram help to find CNS abnormality early and manage accordingly.Correlation of CNS abnormality with gestational age. Correlation of CNS abnormality with neonatal outcome.All seriously ill neonates admitted to Neonatal ICU will be chosen as per the inclusion criteria on selective pattern and neurosonogram will be done by radiologist on particular days. If neurosonography reveals any positive findings, baby will be review up for any sequelae. Follow up neurosonogram will be done in the case of presence of any finding. Neonates will be followed till cured and discharge from Neonatal ICU.The chance of neurosonogram abnormalities in high-risk neonates is more compared to normal neonate. Intracranial bleed, cerebral edema, periventricular leukomalacia, hyperechogenic thalami, ventriculomegaly are some are findings.neurosonogram help to detect early cns abnormality in critical ill neonates.